Agile and Lean practices stand-ups, user stories, and retrospectives - LeMay, Matt (O'Reilly Media, Inc., 2018)
In many cases, organizations first approach "Agile" by implementing specific rituals such as stand-up meetings, user stories, and retrospectives. This video explores some of the most common Agile rituals, and ties them back to the core values of Agile and Lean